Answer:
(18) a. The value of k is 10.
b. The second root is 2.
(19) a. The value of k is -10.
b. The second root is -2.
(20) a. The value of k is -28.
b. The second root is -4.
Explanation
18. One of the roots is 5, :. x = 5
Substitute x = 5 into the quadratic equation to obtain the value of k.
x² - 7x + k = 0
5² - 7(5) + k = 0
25 - 35 + k = 0
-10 + k = 0
k = 0 + 10 = 10
Factorise the quadratic equation to obtain the value of the second root.
x² - 7x + 10 = 0
x² - 5x - 2x + 10 = 0
(x² - 5x) - (2x + 10) = 0
x(x - 5) -2(x - 5) = 0
(x - 5)(x - 2) = 0
x = 5 or 2
The second root is 2.
19. One of the roots is 5, :. x = 5
Substitute x = 5 into the quadratic equation to obtain the value of k.
x² - 3x + k = 0
5² - 3(5) + k = 0
25 - 15 + k = 0
10 + k = 0
k = 0 - 10 = -10
Factorise the quadratic equation to obtain the value of the second root.
x² - 3x + (-10) = 0
x² - 3x - 10 = 0
x² - 5x + 2x - 10 = 0
(x² - 5x) + (2x - 10) = 0
x(x - 5) +2(x - 5) = 0
(x - 5)(x + 2) = 0
x = 5 or -2
The second root is -2.
20. One of the roots is 7, :. x = 7
Substitute the value of x into the quadratic equation to obtain the value of k.
x² - 3x = -k
7² - 3(7) = -k
49 - 21 = -k
28 = -k
k = -28
Factorise the quadratic equation to obtain the value of the second root.
x² - 3x = -k
x² - 3x = 28
x² - 3x - 28 = 0
x² - 7x + 4x - 28 = 0
(x² - 7x) + (4x - 28) = 0
x(x - 7) +4(x - 7) = 0
(x - 7)(x + 4) = 0
x = 7 or -4
The second root is -4.